Investigating the sustainability of the freeway management system and feasibility of implementing a connected vehicle environment in the Western Cape : conceptual design of a connected vehicle environment in Cape Town - Kriel, Aadil (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScEng)--Stellenbosch University, 2017.